Comparison of antioxidant activity in tea drinks using FRAP Assay / Sharifah Nor Hafizai Syed Jaya ...[et al.] - Syed Jaya, Sharifah Nor Hafizai; Mohd Jan, Sarah Laila; Mohd Khazaai, Siti Norhafiza; Zakaria, Siti Raihan; Mat Hussin, Zurhana (2013)
Dangerous effects of free radicals and oxidative stress can be reduced by consistently taking food that produce antioxidant such as flavonoid and other polyphenol compounds. Hence this research was conducted in order to determine the antioxidant activity in tea drink served with sugar or milk as it was a routine drink for some people and cultures. The characterization was done using Attenuated Total Reflectance - Fourier Transform Infrared (ATR-FTIR) spectrometer to identify the antioxidant's presence in tea and antioxidant activity determination were carried out using Ferric Reducing Antioxidant Power (FRAP) assay. ATR-FTIR Spectrum shown the presence of varied numbers of hydroxyl group in several arrangements due to different polyphenols contained in tea powder has distinctive antioxidative properties. The estimation of antioxidant activity was done by using Ultraviolet Visible (UV- VIS) Spectrometer shown that black tea with addition of milk and sugar (BMS) contained the highest antioxidant activity which is 0.467 ug/L compared with black tea (B) and black tea with milk (BM) samples. It is proved that the addition of milk and sugar do not alter the antioxidant activity in tea samples.